SAE Technical Paper Series 2019
DOI: 10.4271/2019-01-0255
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism Triggering Pre-Ignition in a Turbo-Charged Engine

Abstract: Pre-ignition in modern engines is largely attributed to oil-fuel mixture droplets igniting before the spark timing. Researchers have also found pre-ignition events to be triggered by high hydrocarbon emissions from the previous cycle as well as late spark timing in the previous cycle. Additionally, an ideally scavenged engine was not found to be limited by pre-ignition. These observations point to a significant role of residuals in triggering pre-ignition events. Current work studies preignition in a probabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…This idea gained support from experiments that varied the amount of residuals in the engine by varying the exhaust backpressure, and found pre-ignition frequency correlate with mass of residual fraction. The pre-ignition frequency followed the residual mass fraction in such experiments, as well [25]. Other researchers have shown that time-resolved detection of unusually high hydrocarbon emissions during the exhaust stroke indicates unusually high hydrocarbon content in the residual gases that may trigger a preignition event in the next cycle [19,26,27].…”
Section: Results and Discussion: Exploration #1: Pre-ignition Prediction From Exhaust Cycle Ion Signal And Mitigation Strategymentioning
confidence: 77%
“…This idea gained support from experiments that varied the amount of residuals in the engine by varying the exhaust backpressure, and found pre-ignition frequency correlate with mass of residual fraction. The pre-ignition frequency followed the residual mass fraction in such experiments, as well [25]. Other researchers have shown that time-resolved detection of unusually high hydrocarbon emissions during the exhaust stroke indicates unusually high hydrocarbon content in the residual gases that may trigger a preignition event in the next cycle [19,26,27].…”
Section: Results and Discussion: Exploration #1: Pre-ignition Prediction From Exhaust Cycle Ion Signal And Mitigation Strategymentioning
confidence: 77%
“…A modern engine architecture based on AVL 5401 Pre-ignition engine is used for building a GT-Power model. The AVL 5401 engine has been used by the researcher in previous work and details can be found in [27,28]. The GT-Power model is used to simulate the engine with intake pressure ranging from 1 bar (abs) to 4 bar (abs).…”
Section: Methodsmentioning
confidence: 99%
“…Increasing exhaust pressure increases the residual mass, which may carry pre-ignition precursors. Hence, increasing exhaust back pressure (more representative of a real engine) could yield more preignition events [49]. However, when comparing different strategies, a constant backpressure needs to be applied and fixed for all cases (zero in the current study).…”
Section: Methodsmentioning
confidence: 99%
“…Pre-ignition occurrence depends on the probability of activated precursors surviving the exhaust scavenging process (residuals for next cycle) and their ignition in the presence of an ignitable atmosphere [49]. Injecting water in the late exhaust stroke should reduce the probability of the former from occurring (should quench the precursors) while injecting water in the intake and compression strokes would ensure that the latter is reduced (charge cooling effect).…”
Section: Effect Of Water Injection On Pre-ignition Suppressionmentioning
confidence: 99%